(3cfhR GdMbGFb aj MOjK NjQ GdNdGFbs - (3eMeO YHO GdQDha Hf JGL GdYGQajf GHf Ydj Hf Rjf GdYGHOjf GdMOGOj Ke GdefGhj GdbGgQj, Rjf GdOjf ,J (B1031 (3g` s ((3UfYGA s)
(3ChdgG (B:s
(3GdMeO ddg GdPi cSG Cgd GdMOjK QOGA GdTQa hQJHJg Ydi MQha GdeYLe djSgd JfGhdg Ydi GdYQH hGdYLe hSejJg cfhR s
(3BNQgG (B:s
(3Gdjhe EfJbUJ GdYQH edc GdYLe (B( (3ai (B) (3CdG Ef Gdgd ZahQ QMje hCab GdaQGY ef fbd gPG GdSaQ GdLdjd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eNJUQ ajg YTQI BdGa MOjKs
(3HChdgG hBNQgG JedjcGJ efgG eG jQLY Edi SfI (B1174 s
(3cJHJ QehR JNQjL GdCMGOjK HGdMeQI s
(3bQf GdfSN (B:s
Keywords: (3GdMOjK h GdeUWdMs